The initial stages of first-language acquisition begun in adolescence: when late looks early*. Issue 2 (20th January 2012) - RAMÍREZ, NAJA FERJAN; LIEBERMAN, AMY M.; MAYBERRY, RACHEL I.
Abstract : Children typically acquire their native language naturally and spontaneously at a very young age. The emergence of early grammar can be predicted from children's vocabulary size and composition (Bates et al., 1994 ; Bates, Bretherton & Snyder, 1998 ; Bates & Goodman, 1997 ). One central question in language research is understanding what causes the changes in early language acquisition. Some researchers argue that the qualitative and quantitative shifts in word learning simply reflect the changing character of the child's cognitive maturity (for example, Gentner, 1982 ), while others argue that the trajectory of early language acquisition is driven by the child's growing familiarity with the language (Gillette, Gleitman, Gleitman & Lederer, 1999 ; Snedeker & Gleitman, 2004 ). These hypotheses are difficult to adjudicate because language acquisition in virtually all hearing children begins from birth and occurs simultaneously with cognitive development and brain maturation. The acquisition of sign languages, in contrast, is frequently delayed until older ages. In the USA, over 90% of deaf children are born to hearing parents who do not use sign language (Schein, 1989 ). As a result, deaf children are often exposed to sign language as a first language at a range of ages well beyond infancy (Mayberry, 2007 ). In rare cases, some deaf individuals are isolated from all linguistic input until adolescence when they start receiving special services and begin to learn sign language through immersion (Morford, 2003 ). Case studies of language acquisition in such extreme late first-language (L1) learners provide a unique opportunity to investigate first-language learning. The current study investigates three cases of young teens who are in the early stages of acquiring American Sign Language (ASL) as a first language, to determine what first-language acquisition in adolescence looks like.